Hadis dalam Perspektif Ahmad Hassan - Fatih, M (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2013)
The emergence of comprehension to back to the Koran and Sunnah in Indonesia is not only driven by the reality of Islamic beliefs which is mixing with other elements, but also caused by the system of understanding of Islamic teaching which are considered less precise. Call it like understanding the meaning of sunnah, ijtihâd, ittibâ‘, taqlîd, and others. Ahmad Hassan, a Muslim thinker who is affiliated to the organizations that called PERSIS, came up to take a role in the struggle of the above problems. Armed with a depth of knowledge, a breadth of knowledge and mastery of sciences, Hassan appeared to prove that the Koran and Sunnah has been more than adequate as a source of Islamic teachings without requiring additional elements. In this regard, it is important to listen to his ideas in the field of hadith as the second source after the Koran. This simple paper tries to capture the thought of Hassan’s hadith and his contribution to the development of hadith studies in Indonesia.